Comprehensive Study on Silk Sericin and its Biological Uses - Pushpa Yadav (Contemporary Research and Perspectives in Biological Science Vol. 10, 2025)
Silk fibroin and sericin are the two types of proteins that make up silk. Among these two silk proteins present in the cocoon, sericin contributes 20 to 30 percent. Sericin is a by-product of the silk industry that is organic, environmentally benign, proteinaceous and biodegradable. To give raw silk luster, a degumming process must be used to remove the sticky sericin substance. Its solubility and molecular weight depend on how silk sericin is extracted. It has numerous uses in pharmacy, medicine, and cosmetics, including anti-hypertensive, wound-healing, antioxidant, and anti-aging effects.